Structural, optical, and surface morphological studies of ethyl cellulose/graphene oxide nanocomposites. Issue 7 (26th March 2020) - Khichar, Kamal Kumar; Dangi, Suraj Bhan; Dhayal, Vimala; Kumar, Upendra; Hashmi, Sonia Zeba; Sadhu, Veera; Choudhary, Banwari Lal; Kumar, Shalendra; Kaya, Savaş; Kuznetsov, Aleksey E.; Dalela, Saurabh; Gupta, Saral K.; et al.
Abstract: Motivated by the outstanding properties and unique structure of graphene oxide (GO), the polymer nanocomposites of ethyl cellulose (EC) as a polymer matrix and the GO as a nano‐filler have been prepared with the different GO wt% concentrations using simple solution blending technique followed by the ultrasonication treatment and characterized by using various advanced techniques. The X‐ray diffraction (XRD) was utilized to determine the preliminary phase determination and for the structural analysis. The optical band gaps were determined with the help of UV‐Vis‐NIR spectrophotometer and were verified by the PL spectra using Spectro‐Fluorescence. According to experimental results, the optical bandgap of the nanocomposite was found to reduce with increasing GO content. The field emission scanning electron microscopy (FESEM) was used to study the surface morphology and to identify the presence of GO in the nanocomposites. The Fourier transform infrared (FTIR) study has been carried out to recognize the presence of functional groups and their vibrational mechanisms. Micro‐Raman imaging technique has been used to determine the Raman bands present in the nanocomposites. The optical band gap of the nanocomposites reflects the semiconducting nature, which might be used in optoelectronic devices and sensor applications.